Persepsi Ibu Tentang Pemberian Asi Lanjutan (0-2 Tahun): Studi Fenomenologi - Luh Ayu Purnami; Lina Anggaraeni Dwijayanti; Putu Sukma Megaputri; Luh Vina Utari; Putu Dinda Marda Cahyadi Putri (2020)
Growth and development of infants can not be separated from the provision of nutrients provided, including breastfeeding on an ongoing basis. Advanced breastfeeding is optimal breastfeeding until the age of 2 years. This study aims to explore in depth the mothers' perceptions about the continued breastfeeding. This research is a type of qualitative research with phenomenological approach conducted in six villages in the work area of the Sawan I Health Center, namely Bungkulan, Sangsit, Giri Emas, Kerobokan, Sinabun, Suwug, and Sudaji Villages. Data collection techniques were open and in-depth interviews of 421 people in each village in January-August 2018. There were eight phenomena that were found, namely participants who were unable to breastfeed, did not have much time to breastfeed optimally for up to two years, had the perception that Breastmilk issued is not smooth and minimal, must return to work (insufficient time off work), knowledge and understanding of the optimal and ideal time for breastfeeding Continued for up to two years, promotion of formula milk is very interesting, and do not know alternative ways of storing breast milk that is effective.